2017
DOI: 10.1111/sed.12284
|View full text |Cite
|
Sign up to set email alerts
|

Sedimentology of coexisting travertine and tufa deposits in a mounded geothermal spring carbonate system, Obruktepe, Turkey

Abstract: The recent discoveries of deeply buried Cretaceous reservoir bodies in the Atlantic Ocean revealed that relationships between the distribution of spring carbonate deposits and faults are poorly understood. The well‐exposed Quaternary deposits at Obruktepe (Denizli Basin, Turkey) provide an opportunity to reconstruct the three‐dimensional sedimentary architecture of such a system. Integration of sedimentological, lithofacies and geochemical analyses reveals complexity in the lateral relationships between sedime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…2) suggests rapid decay in precipitation potential with distance from the source of hydrothermal fluids (e.g. Dekov et al, 2014;Lopez et al, 2017). Firstly, the onset of hydrothermal activity was marked by formation of laminae or bands of Md dolomites intercalated with unconsolidated lacustrine sediments layers, giving way up-section to deposition of intermixed muds/silts and Md dolomites.…”
Section: Genetic Model For Syn-sedimentary Hydrothermal Dolomitesmentioning
confidence: 99%
“…2) suggests rapid decay in precipitation potential with distance from the source of hydrothermal fluids (e.g. Dekov et al, 2014;Lopez et al, 2017). Firstly, the onset of hydrothermal activity was marked by formation of laminae or bands of Md dolomites intercalated with unconsolidated lacustrine sediments layers, giving way up-section to deposition of intermixed muds/silts and Md dolomites.…”
Section: Genetic Model For Syn-sedimentary Hydrothermal Dolomitesmentioning
confidence: 99%
“…), dissolution Lopez et al (2017), Westaway (1993), Pentecost et al (1997), Kele et al (2011), De Filippis et al (2012, Özkul et al (2013), Van Noten et al (2013), Lebatard et al (2014), Claes et al (2015Claes et al ( , 2017aClaes et al ( , 2017b Sorey and Colvard (1997), Fouke et al (2000Fouke et al ( , 2003, Kharaka et al (2000), Chafetz and Guidry (2003), Kandianis et al (2008), Veysey et al (2008) Cipriani et al (1977), Barazzuoli et al (1988), Guo and Riding (1992, Pentecost (1995), Minissale et al (2002), Brogi et al (2007), Brogi and Capezzuoli (2008), Pedley (2009), Gandin and Capezzuoli (2014) Arp et al (2001Arp et al ( , 2010, Shiraishi et al (2008aShiraishi et al ( , 2008b, Brinkmann et al (2015) (continued on next page) et al, 2012; Nielsen et al, 2014). Lab and field studies report ACC phases found in close association with crystalline CaCO 3 (Jones and Peng, 2012a;Pedley, 2014) and/or organisms (cyanobacteria) or organic substances (Couradeau et al, 2012;Benzerara et al, 2014;Martignier et al, 2017).…”
Section: Tablementioning
confidence: 99%
“…These facies also record microbial growth in the zones characterized by different physical and chemical conditions determined by degassing, the influx of cation-rich groundwater and evaporative concentration of ions in the splash zones. Microbial growth in the presence of standing bodies of water creates additional recognizable facies, including mounds, pools, terracettes, palmate tufa towers, streamers, cascading overhangs, rafts, encrusted pebbles, small and large columnar thrombolites and stromatolites, coated bubbles, shrubs, ooids, pisoids, spherulites and other structures [160][161][162][163][164][165][166][167][168][169][170][171][172][173][174][175][176] .…”
Section: Non-marine Carbonate Depositsmentioning
confidence: 99%
“…In Lake Salda, diatoms and cyanobacteria appear to be the principal builders of cm-thick gelatinous coatings that cover stromatolites, ultramafic rocks or wood and contain microcrystalline platy hydromagnesite 166,228 . The association of microcrystalline and nanocrystalline hydromagnesite with alveolar EPS and sheaths of filamentous cyanobacteria indicate that the activities of organisms and processes that produce and degrade EPS strongly control the precipitation of this mineral 169,182,[228][229][230] . The exposed stromatolites and stromatolites that lack microbial coatings in Lake Salda, as well as the exposed microbial mats in playa lakes, are porous, friable and thought to be susceptible to erosion 166,225,231 .…”
Section: Microbial Textures In Magnesium Carbonatesmentioning
confidence: 99%